2021
DOI: 10.3390/ijerph18179009
|View full text |Cite
|
Sign up to set email alerts
|

Exploring a Complementary Stress Management and Wellbeing Intervention Model for Teachers: Participant Experience

Abstract: Background: work-related stress can have alarming physiological and psychological health impacts, which may permeate into personal and professional contexts. Teachers need to be supported to develop the skills and strategies to effectively identify how stress manifests and how to use simple, practical techniques to manage and reduce the impact of stress. Complementary interventions (CIs) for educators may provide stress management and assist with supporting wellbeing at the individual level. Methods: the conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 75 publications
0
20
0
1
Order By: Relevance
“…An intervention study about complementary stress management and well-being for teachers showed experienced benefits in personal and professional settings, behavioral changes, increased awareness of the impact of stress, and a decrease in the stress response. 52 The results obtained in this study are limited in some other aspects, which will be briefly discussed in the following. The German teachers were significantly older than the Ukrainian teachers.…”
Section: Discussionmentioning
confidence: 96%
“…An intervention study about complementary stress management and well-being for teachers showed experienced benefits in personal and professional settings, behavioral changes, increased awareness of the impact of stress, and a decrease in the stress response. 52 The results obtained in this study are limited in some other aspects, which will be briefly discussed in the following. The German teachers were significantly older than the Ukrainian teachers.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, teachers’ well-being and care for mental health positively impact their students’ academic self-perception, well-being, and potential distress [ 31 , 32 ]. It is essential to support teachers with skills to prevent mental health deterioration [ 33 ], and many teachers supporting models have been proposed [ 32 , 34 , 35 ]. Garcia-Alvarez et al indicated the importance of active interventions based on positive psychology in private and professional life and the promotion of well-being approaches [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The term stress itself comes from the Latin term, namely from the word stringere which means tension and pressure. Stress is an inherent part of life (Hepburn et al, 2021). Anyone and anywhere, in different levels of light weight and in unequal periods of time, has or will experience it.…”
Section: Stress Management Strategiesmentioning
confidence: 99%